COMPARISON OF BOUNDARY AND VOLUME BASED REPRESENTATION TYPES IN 3D GRAPHICS APPLICATION AREAS - Nurimov, P.B.; Isakov, I.O. (ILIM hám JÁMIYET, 2025)
The article compares boundary-based and volume-based 3D representation methods. Boundary-based techniques, like meshes and NURBS, excel in surface detail for animation and gaming, while volume-based methods, such as voxels and CSG, are ideal for internal analysis in medical imaging and engineering. The study explores their strengths, limitations, and hybrid potential.